Pedagogical Grammar in an Indonesian ELT Textbook: Features, Approaches, and Design Criteria Analysis - Jasrial, Dedi; Jufrizal, Jufrizal; Eang, Norphealey (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
Numerous researchers have delved into the intricacies of grammar, yet the analysis of pedagogical grammar in EFL textbooks has been sorely neglected. This study aims to examine the pedagogical grammar features of an Indonesian English as a Foreign Language (EFL) textbook intended for seventh-graders, the teaching approaches employed to convey those features, and the criteria used to design the pedagogical language rules incorporated in the pedagogical grammar features. This mixed-method research used an EFL textbook for seventh-graders in Indonesia as the source of data that were collected using observation sheets and a checklist based on Swan's theory regarding design criteria for pedagogical language rules. The data were analyzed qualitatively (descriptive qualitative technique) and quantitatively (descriptive statistics). This study found that the Indonesian EFL textbook contained simple present tense and 14 pedagogical grammar features. The textbook utilized both inductive and deductive approaches to deliver pedagogical grammar features, with the deductive approach being the most used. The design criterion of pedagogical language in the textbook was evaluated to be of high quality. Thus, it can be concluded that the analyzed textbook is a suitable learning resource for Indonesian EFL teachers, especially those who wish to focus on pedagogical grammar.